2019
DOI: 10.1155/2019/1296248
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Plastic Shrinkage Cracking of Self‐Compacting Concrete

Abstract: Concrete exposed to hot climatic conditions is prone to plastic shrinkage after casting within the first few hours due to the water evaporation and restraining conditions of concrete. This cracking is more commonly observed in concrete elements with a large surface area exposed to drying. In this research, plastic shrinkage of 13 self-compacting concrete samples with different cement paste volumes and various coarse to total aggregate ratios was studied. Test specimens of fresh concrete were subjected to a win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The model was built based on a large amount of experimental data. Ghoddousu et al [20] developed an equation to estimate plastic shrinkage values based on the coarse aggregate ratio and W/P ratio under hot-dry climate conditions. The results showed that plastic shrinkage depends on time and has a linear relationship with evaporable water content.…”
Section: Introductionmentioning
confidence: 99%
“…The model was built based on a large amount of experimental data. Ghoddousu et al [20] developed an equation to estimate plastic shrinkage values based on the coarse aggregate ratio and W/P ratio under hot-dry climate conditions. The results showed that plastic shrinkage depends on time and has a linear relationship with evaporable water content.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, researchers used a wind tunnel for this simulation. Ghoddousi Parviz et al [27] specified the preparation of 13 self-compacting concrete samples, which were made according to different mixing designs. These samples were placed inside a wind tunnel, which simulated warm and dry environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…UHPC with a different mix design model is a combination of portland cement, sand, quartz powder, silica fume, superplasticizer, water, and steel fibres [4,[8][9][10][11]. In the UHPC mixture, a higher portion of cement is used compared to the HPC and normal strength concrete (NSC) [12,13] and the key factor of UHPC production is the enhancement of material density, mechanical homogeneity, and particle packing by improving macro and micro properties [12][13][14][15][16][17][18][19][20], which help the durability of UHPC against chloride diffusion. The water-to-cement ratio (W/C) of UHPC is typically less than 0.25 due to the replacement of the portion of un-hydrated cement with blast furnace slag, fly ash, or crushed quartz [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%